The perception of risk related to complications and its relation with metabolic parameters in diabetic individuals - Karakoc Kumsar, Azime; Taskin Yilmaz, Feride; Celik, Selda; Bagdemir, Elif (Annals of Medical Research, 2021)
Aim: For an efficient disease management and prevention of the development of complication, diabetic individuals are expected to establish a new life style right from the diagnosis. The perception of risk related to the disease has importance in the adaptation of the diabetic individuals to the new life style. The research is conducted to identify the perception of risk related to complications and it’s relation with metabolic parameters in diabetic individuals.Materials and Methods: This descriptive research was conducted in 237 diabetic individuals applied to a Diabetes Polyclinic of a university hospital. The data was acquired by patient identification form, The Risk Perception Survey–Diabetes Mellitus Scale and metabolic control variables form.Results: Individuals’ knowledge of the risk related to diabetic complications are at a good level while the perceived risk level is high. It is particularly confirmed that individuals perceive complications such as heart attack, high blood pressure and vision problems risky at a higher level. A positive correlation is established between the period of disease and risk knowledge, HbA1c level and worry, and fasting blood sugar and risk perception (p0.01).Conclusion: In the study, it is determined that, despite the high level of risk knowledge related to complications, the diabetic management of individuals is not enough while the risk perception is high. It is confirmed that the risk perception of metabolic parameters is especially related to worry level.